Cross-talk of nitric oxide and reactive oxygen species in plant programed cell death - Wang, Yiqin; Loake, Gary J.; Chu, Chengcai (Frontiers in Plant Science, 2013)
In plants, programed cell death (PCD) is an important mechanism to regulate multiple aspects of growth and development, as well as to remove damaged or infected cells during responses to environmental stresses and pathogen attacks. Under biotic and abiotic stresses, plant cells exhibit a rapid synthesis of nitric oxide (NO) and a parallel accumulation of reactive oxygen species (ROS). Frequently, these responses trigger a PCD process leading to an intrinsic execution of plant cells. The accumulating evidence suggests that both NO and ROS play key roles in PCD. These redox active small molecules can trigger cell death either independently or synergistically. Here we summarize the recent progress on the cross-talk of NO and ROS signals in the hypersensitive response (HR), leaf senescence and other kinds of plant PCD caused by diverse cues.